2021
DOI: 10.3390/biomedicines9050560
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fatty Acid-Binding Proteins in α-Synuclein-Induced Mitochondrial Injury in Synucleinopathy

Abstract: Synucleinopathies are diverse diseases with motor and cognitive dysfunction due to progressive neuronal loss or demyelination, due to oligodendrocyte loss in the brain. While the etiology of neurodegenerative disorders (NDDs) is likely multifactorial, mitochondrial injury is one of the most vital factors in neuronal loss and oligodendrocyte dysfunction, especially in Parkinson’s disease, dementia with Lewy body, multiple system atrophy, and Krabbe disease. In recent years, the abnormal accumulation of highly n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 149 publications
(191 reference statements)
0
7
0
Order By: Relevance
“…Increased concentrations of B-FABP are associated with human brain tumors (e.g., glioblastoma and astrocytoma), neurodegenerative diseases (Alzheimer’s disease and PD), and other cognitive dysfunctions ( Choromańska et al, 2011 ). A series of studies suggest that FABP3, FABP5, and FABP7 play important roles in α-synuclein oligomerization and migration, trigger the loss of neuronal mitochondrial function, and even interact with VDAC-1 to modulate the formation of channel pores in the mitochondrial membrane ( Kawahata et al, 2019 ; Matsuo et al, 2019 ; Cheng et al, 2021 ; Kawahata and Fukunaga, 2022 ). Thus, FABP is considered a promising therapeutic target for α-synucleinopathies ( Kawahata and Fukunaga, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increased concentrations of B-FABP are associated with human brain tumors (e.g., glioblastoma and astrocytoma), neurodegenerative diseases (Alzheimer’s disease and PD), and other cognitive dysfunctions ( Choromańska et al, 2011 ). A series of studies suggest that FABP3, FABP5, and FABP7 play important roles in α-synuclein oligomerization and migration, trigger the loss of neuronal mitochondrial function, and even interact with VDAC-1 to modulate the formation of channel pores in the mitochondrial membrane ( Kawahata et al, 2019 ; Matsuo et al, 2019 ; Cheng et al, 2021 ; Kawahata and Fukunaga, 2022 ). Thus, FABP is considered a promising therapeutic target for α-synucleinopathies ( Kawahata and Fukunaga, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that the increase in CaMKII autophosphorylation levels induced by QNP stimulation was significantly inhibited by MF1 treatment, which was observed in cultured NAc slices from WT but not D2R null mice, suggesting that MF1 prevents CaMKII autophosphorylation by inhibiting D2Rs. FABP3 interacts and colocalizes with D2LR in vitro and in vivo [ 30 , 31 , 58 , 59 ]. Therefore, MF1, an FABP3 inhibitor, may also inhibit D2R/FABP3 function.…”
Section: Discussionmentioning
confidence: 99%
“…FABP3, FABP5, and FABP7 are expressed in the brain. Many studies have linked these three FABP subtypes to neuronal damage and inflammatory pathways in various neurodegenerative disorders [ [15] , [16] , [17] , [18] , [19] ]. Abnormal FABP expression occurs in patients with neurodegenerative diseases, such as Alzheimer's and Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%